Zein / polyoxyethylene / dihydroquercetin nanofiber preservative film as well as preparation method and application thereof
By blending zein, polyethylene oxide and dihydroquercetin, nanofiber plastic wrap is prepared, which solves the problem of insufficient biological activity of nanofiber plastic wrap in the prior art, and realizes nanofiber plastic wrap in meat Improved versatility in freshness.
Patent Information
- Application Number
- CN202411589331.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In the prior art, the biological activity of nanofiber plastic wrap in meat preservation has not been fully explored, especially flavonoids such as dihydroquercetin, which has a variety of biological activities, are not found in nanofiber plastic wrap.
Blend zein, polyethylene oxide and dihydroquercetin to prepare nanofiber plastic wrap by solution blow-press spinning technology. The antioxidant and antibacterial properties of dihydroquercetin are used to enhance nanofiber plastic wrap biological activity.
The prepared zein/polyethylene oxide/dihydroquercetin nanofiber plastic wrap has the advantages of good flexibility, hydrophobicity, antioxidant, antibacterial, biocompatibility, environmental protection and degradability, etc., and is suitable for Food packaging materials and biomedical fields.
Smart Images

Figure CN119465511A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of bio-based polymer composite materials, and in particular to a zein / polyethylene oxide / dihydroquercetin nanofiber cling film and a preparation method and application thereof. Background Art
[0002] Solution blow spinning (SBS) is an emerging method for rapidly preparing nanofibers with high specific surface area, good loading capacity and high porosity. SBS uses high-speed airflow to stretch polymer solutions into filaments, and the stretching process is accompanied by the volatilization of some solvents. The filaments are then collected by rolling on a receiver to form a nanofiber film. Compared with electrospinning, the most popular nanofiber production technology, SBS has the advantages of high production efficiency, low cost, and no requirement for high voltage supply.
[0003] Nanofiber cling film, as a nanomaterial, is a fibrous network structure formed by hydrophilic macromolecules or polymers through molecular interactions such as hydrogen bonds, hydrophobic interactions or van der Waals forces. Its nanometer diameter can increase the drug loading rate and has a high specific area and high porosity.
[0004] Zein is a renewable natural high-molecular protein extracted from corn. It mainly exists in the endosperm of corn. It is a byproduct of corn deep processing and has a wide range of sources. Zein has good film-forming, antioxidant and gelling properties and has been used as a surface material and protective pharmaceutical material. In addition, zein has a polypeptide structure that gives it the unique advantages of biodegradability and biocompatibility.
[0005] Nanofilms with various structures and functions can be designed and constructed by using technologies such as solution blowing and spinning, such as pH-responsive nanofilms, CO2-responsive nanofilms, antibacterial nanofilms, etc. Adding polyethylene oxide can improve the fiber formation, while also improving the brittleness of the zein raw material itself, enhancing the mechanical properties and flexibility, and broadening its application areas.
[0006] Dihydroquercetin (DHQ), also known as taxol, is a larch extract and an important flavonoid compound. It has antibacterial, anticancer, anti-inflammatory, antiviral, antioxidant, anti-fibrotic, hypoglycemic and immune-regulating effects, melanin removal and anti-cardiovascular disease effects. In recent years, flavonoids such as luteolin and apigenin have been studied and added to nanofiber cling film to enhance the biological activity of the film. However, dihydroquercetin, known as the "king of cleansing" among flavonoids, has not been introduced into nanofiber cling film to explore its effect on meat preservation.
[0007] Therefore, it is of great significance to introduce dihydroquercetin with antioxidant and antibacterial properties combined with polyethylene oxide with good biocompatibility and easy processability into renewable zein raw materials to prepare a nanofiber cling film with good biocompatibility and good mechanical properties, as well as multifunctional properties such as hydrophobicity, antioxidant, antibacterial, and UV resistance. Summary of the invention
[0008] In view of this, the embodiments of the present application provide a zein / polyethylene oxide / dihydroquercetin nanofiber cling film and a preparation method and application thereof. The nanofiber cling film has good hydrophobicity and antioxidant capacity, and at the same time has the advantages of good flexibility, hydrophobicity, antioxidant, antibacterial property, biocompatibility and environmental protection and degradability. It can be widely used in food packaging materials and biomedicine and other fields. Therefore, it has good application prospects and can effectively overcome the defects of the above-mentioned prior art.
[0009] The first aspect of the embodiment of the present application provides a method for preparing a zein / polyethylene oxide / dihydroquercetin nanofiber cling film, comprising the following steps:
[0010] Zein is dissolved in an acetic acid solution, polyethylene oxide is then added to obtain a zein / polyethylene oxide blended solution, dihydroquercetin is added to the zein / polyethylene oxide blended solution, and the mixture is evenly mixed to obtain a spinning solution; the spinning solution is subjected to a solution blowing spinning process to obtain a zein / polyethylene oxide / dihydroquercetin nanofiber cling film.
[0011] The polyethylene oxide (PEO) polymer chain interacts with the amino and carboxyl groups in zein through intermolecular hydrogen bonds, increasing the viscosity and stability of the spinning solution, making the nanofibers more stable and uniform during the spinning process, while increasing the mechanical strength, toughness and flexibility of the film; the addition of dihydroquercetin (DHQ) improves the antioxidant properties of the nanofiber cling film, and its good antibacterial properties can reduce the growth of microorganisms on the surface of the nanofiber cling film.
[0012] In some embodiments that may include the above embodiments, the specific process of the solution blowing spinning process is:
[0013] Transfer part of the spinning solution to the injection container, bend the needle head to 90° and install it on the micro-injection pump, adjust the solution advancement speed, turn on the air compressor for blowing, adjust the spinning air pressure and receiving distance, and stick a circle of release paper on the receiver for subsequent separation, adjust the receiver speed, click the start button on the injection pump, and start spinning.
[0014] In some embodiments, which may include the above embodiments, the parameters of the solution blowing spinning process are:
[0015] The injection container is a 5 mL syringe, the needle model is 30G, the solution advancement speed is 1 mL / h, the spinning gas pressure is 0.020 MPa, the receiving distance is 50 cm, and the receiver rotation speed is 100 r / min.
[0016] In some embodiments that may include the above embodiments, the mass ratio of zein, polyethylene oxide, and dihydroquercetin is 2:0.1:(0.1-0.4).
[0017] In some embodiments that may include the above-mentioned embodiments, the specific preparation process of the spinning solution is: after the acetic acid solution is prepared, zein is first added in proportion, stirred for 3 minutes until there is no lumpy powder, and then polyethylene oxide is added. After mixing evenly until there are no obvious lumpy particles, dihydroquercetin is added while stirring, and stirred at room temperature overnight until it is completely dissolved to obtain a spinning solution.
[0018] In some embodiments, which may include the above embodiments, the volume ratio of acetic acid to water in the acetic acid solution is 8:2.
[0019] Preferably, the preparation method of the zein / polyethylene oxide / dihydroquercetin nanofiber cling film of the present application specifically comprises the following steps:
[0020] (1) Preparation of zein / polyethylene oxide / dihydroquercetin spinning solution: In a 20 mL beaker, first add 8 mL of acetic acid, then add 2 mL of deionized water, mix well and start stirring on a stirrer, then add 2 g of zein while stirring, then add 0.1 g of polyethylene oxide while stirring, after it is completely dispersed, add 0.1-0.4 g of dihydroquercetin, also while stirring, stir at room temperature overnight until dissolved, to obtain a spinning solution;
[0021] (2) Preparation of zein / polyethylene oxide / dihydroquercetin nanofiber cling film: transfer part of the prepared spinning solution to a 5 mL syringe, use a 30G needle, bend its head to 90°, install it on a micro-injection pump, adjust the solution propulsion speed to 1 mL / h, turn on the air compressor for blowing, and adjust the spinning air pressure to 0.020 MPa, adjust the receiving distance to 50 cm, and stick a circle of release paper on the receiver to facilitate subsequent separation, adjust the receiver speed to 100 r / min, click the start button on the injection pump to start spinning, and obtain zein / polyethylene oxide / dihydroquercetin nanofiber cling film.
[0022] It should be noted that in the preparation method of the present application, zein is added first, and then polyethylene oxide is added, so that the first two can interact with each other first, increasing the viscosity and spinnability of the solution, and then dihydroquercetin is added and fully stirred. By utilizing the self-sealing property of zein, part of the dihydroquercetin can be embedded therein. In addition, the addition of dihydroquercetin enhances the antioxidant, antibacterial and other biological activities of the nanofiber cling film.
[0023] The second aspect of the embodiment of the present application also provides a zein / polyethylene oxide / dihydroquercetin nanofiber cling film, which is prepared by the above method. The zein / polyethylene oxide / dihydroquercetin nanofiber cling film has the advantages of good flexibility, hydrophobicity, antioxidant, antibacterial, biocompatibility, UV resistance, environmental protection and degradability.
[0024] In some embodiments, which may include the above embodiments, the fibers in the nanofiber cling film are uniformly distributed and have a diameter of 360 nm.
[0025] The third aspect of the embodiments of the present application also provides the application of the above-mentioned zein / polyethylene oxide / dihydroquercetin nanofiber cling film in food packaging materials and biomedicine.
[0026] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0027] (1) The reaction conditions of the preparation method of the present application are room temperature, the required equipment is simple, the preparation efficiency is high and the controllability is strong;
[0028] (2) The preparation method of the present application is a nanofiber cling film system, which provides a larger specific surface area and extremely fine nanofibers, and increases the amount of dihydroquercetin loaded thereon. In addition, the polymer chain of polyethylene oxide interacts with the amino and carboxyl groups in zein through hydrogen bonds, which increases the viscosity and stability of the solution, making the nanofibers more stable and uniform during the spinning process, and improving the brittleness of zein to a certain extent, giving the nano packaging film a wider range of applications;
[0029] (3) The present application constructs a novel multifunctional antibacterial, antioxidant, and hydrophobic nanofiber cling film integrating multiple functional components by blending zein and polyethylene oxide with the drug dihydroquercetin system. The novel nanofiber cling film has good biocompatibility and has a wide application prospect as a food packaging material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 The scanning electron microscope image and diameter distribution diagram of the surface of the nanofiber cling film prepared in Comparative Example 1;
[0032] Figure 2 The water contact angle diagrams of the nanofiber cling film prepared in Comparative Example 1 and Examples 1-4;
[0033] Figure 3 The ultraviolet transmittance graph of the nanofiber cling film prepared in Comparative Example 1 and Examples 1-4;
[0034] Figure 4 The scavenging rate graphs of DPPH free radical and ABTS free radical of the nanofiber cling film prepared in Comparative Example 1 and Examples 1-4;
[0035] Figure 5 (a) is a graph showing the antibacterial performance of the nanofiber cling film obtained in Examples 1-4. Figure 5 (b) is a photo of the antibacterial zone test of the nanofiber cling film prepared in Examples 1-4. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0037] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0038] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0039] Example 1
[0040] (1) Preparation of Zein / Polyethylene Oxide / Dihydroquercetin Spinning Solution:
[0041] Weigh 2 g of zein and dissolve it in a mixed solution of 8 ml of acetic acid and 2 ml of deionized water, then add 0.1 g of polyethylene oxide while stirring. After it is completely dispersed, add 0.1 g of dihydroquercetin and stir at room temperature overnight until it is dissolved to obtain a spinning solution of zein / polyethylene oxide / dihydroquercetin.
[0042] (2) Preparation of Zein / Polyethylene Oxide / Dihydroquercetin Nanofiber Fresh-keeping Film:
[0043] Transfer the prepared spinning solution to a 5mL syringe, use a 30G needle, bend its head to 90°, install it on a micro-injection pump, adjust the solution advancement speed to 1mL / h, turn on the air compressor for blowing, and adjust the spinning air pressure to 0.020MPa, adjust the receiving distance to 50cm, and stick a circle of release paper on the receiver to facilitate subsequent separation, adjust the receiver speed to 100r / min, click the start button on the injection pump, and spinning begins. Wait for 5h to get a nanofiber cling film with a thickness of about 0.10mm, recorded as ZPD-1%.
[0044] Example 2
[0045] The zein / polyethylene oxide / dihydroquercetin nanofiber cling film and its preparation method of this embodiment can refer to Example 1, except that 0.2 g of dihydroquercetin is added, which is recorded as ZPD-2%.
[0046] Example 3
[0047] The zein / polyethylene oxide / dihydroquercetin nanofiber cling film and its preparation method of this embodiment can refer to Example 1, except that 0.3 g of dihydroquercetin is added, which is recorded as ZPD-3%.
[0048] Example 4
[0049] The zein / polyethylene oxide / dihydroquercetin nanofiber cling film and the preparation method thereof of this embodiment can refer to Example 1, except that 0.4 g of dihydroquercetin is added, which is recorded as ZPD-4%.
[0050] Comparative Example 1
[0051] (1) Weigh 2 g of zein and dissolve it in a mixed solution of 8 ml of acetic acid and 2 ml of deionized water, then add 0.1 g of polyethylene oxide, add while stirring, and stir at room temperature overnight until dissolved, to obtain a zein / polyethylene oxide spinning solution.
[0052] (2) The prepared spinning solution was transferred to a 5 ml syringe, and a 30G needle was used. The needle head was bent to 90° and installed on a micro-injection pump. The solution propulsion speed was adjusted to 1 mL / h. The air compressor was turned on for blowing, and the spinning pressure was adjusted to 0.020 MPa. The receiving distance was adjusted to 50 cm, and a release paper was pasted on the receiver for subsequent separation. The receiver speed was adjusted to 100 r / min. The start button on the injection pump was clicked, and spinning began. After waiting for 5 h, a nanofiber cling film with a thickness of about 0.10 mm was obtained, which was recorded as ZP.
[0053] (3) After the zein / polyethylene oxide nanofiber cling film was woven, the film surface was observed by scanning electron microscopy and photographed at 20.00K×. The results are as follows: Figure 1 shown.
[0054] Depend on Figure 1 It can be seen that the fiber diameter is uniform, the distribution is consistent, and the fibers are tightly interwoven with good directionality. This structure is conducive to loading more drugs and enhancing the functionality of the membrane.
[0055] Test Example 1
[0056] The hydrophobicity test of the nanofiber cling film in Examples 1-4 and Comparative Example 1
[0057] Water contact angle test: Take three 1.0cm×1.0cm samples of each of the five nanofiber cling films and place them on the test plate. Use an interfacial tension analyzer to test the contact angle. Then gently drop 0.005ml of distilled water on the film surface. Use a video monitor to measure the change in contact angle within 2s after dripping water. Select pictures with representative changes to determine the wettability of the samples. The results are as follows: Figure 2 shown.
[0058] Figure 2 is the water contact angle diagram, through Figure 2 It can be seen that the contact angle of the zein / polyethylene oxide film (abbreviated as ZP) in Comparative Example 1 is 128.2°, and after adding different masses of dihydroquercetin, the contact angles of the zein / polyethylene oxide / dihydroquercetin films in Examples 1-4 are 121.3°, 116.5°, 118.2°, and 111.9°, respectively. The contact angle has changed, but is still greater than 90°. Therefore, the nanofiber cling film of Examples 1-4 has excellent hydrophobic properties.
[0059] Test Example 2
[0060] Light transmission performance test of the nanofiber cling film in Examples 1-4 and Comparative Example 1
[0061] Light transmittance test: Cut the above five nanofiber cling films into a size of 1.0 cm × 5.0 cm, place them in a quartz cuvette, and use an ultraviolet spectrophotometer to scan the film in the range of 200-700 nm. The calculation formula is: Light transmittance T (%) = 10 -A , where A is the measured UV-visible spectrophotometer value, the result is as follows Figure 3 shown.
[0062] Figure 3 is the ultraviolet transmittance diagram of the film, through Figure 3 It can be seen that the transmittance in the UV-C (200-275nm), UV-B (275-320nm) and UV-A (320-420nm) regions is close to 0%, while in the visible light region, the transmittance of the ZP film is the lowest because zein is an optically opaque polymer. With the increase of DHQ (dihydroquercetin), the transmittance gradually increases, but the maximum transmittance is only about 0.8%, which proves that the nanofilms of Examples 1-4 have good UV barrier properties.
[0063] Test Example 3
[0064] Antioxidant performance test of the nanofiber cling film in Examples 1-4 and Comparative Example 1
[0065] DPPH free radical scavenging ability test: Weigh 0.01g of different nanofiber membranes and dissolve them in 10mL of anhydrous ethanol to prepare a 1mg / mL fiber membrane sample solution. Mix 2mL of sample with 2mL of 0.1mM DPPH dissolved in anhydrous ethanol, mix 2mL of sample solution with 2mL of anhydrous ethanol solution, and measure the absorbance of 2mL of anhydrous ethanol solution and 2mL of DPPH solution. Mix them thoroughly and store them away from light for 40min. The DPPH free radical scavenging ability of the nanofiber cling film is calculated by the absorbance at 517nm. The specific results are shown in Figure 4 .
[0066] ABTS free radical scavenging ability test: ABTS (0.0384g) and K2S2O8 (0.0134g) were dissolved in 10mL of deionized water to obtain ABTS and K2S2O8 solutions, respectively. The two reagents were then mixed in a 1:1 ratio and protected from light for 12h, and then diluted with PBS at pH 7.4 to an absorbance of 0.70±0.02, i.e., ABTS working solution; 5mg of different nanofiber membranes were weighed and dissolved in anhydrous ethanol as sample solution; 0.8mL of ABTS working solution and 0.2mL of anhydrous ethanol were taken, mixed and shaken for 10s, allowed to stand for 6min, and A1 was measured at 734nm; 0.8mL of ABTS working solution and 0.2mL of sample solution were taken, mixed and shaken for 10s, allowed to stand for 6min, and A2 was measured at 734nm. The calculation formula is:
[0067] ABTS clearance rate (%) = (A1-A2) / A1×100%. For specific results, see Figure 4 .
[0068] Figure 4 This is a test chart of the antioxidant effect. Figure 4 It can be seen that after adding dihydroquercetin, the zein / polyethylene oxide / dihydroquercetin nanofiber packaging film has good antioxidant properties, the DPPH free radical scavenging rate is more than 90%, and the ABTS free radical scavenging rate increases with the increase of concentration, and the highest scavenging rate is as high as 91.22%.
[0069] Test Example 4
[0070] Antibacterial performance test of the nanofiber cling film in Examples 1-4 and Comparative Example 1
[0071] Antibacterial performance test of dihydroquercetin: The inhibitory activity of dihydroquercetin against was determined by the agar plate punching method. The four foodborne bacteria tested were specifically Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Vibrio parahaemolyticus. Use 20% (volume fraction, the same below) DMSO to dissolve dihydroquercetin and add it to sterile water to make the concentration of dihydroquercetin 1% (10 mg / mL), 2% (20 mg / mL), 3% (30 mg / mL), 4% (40 mg / mL) (corresponding to Examples 1-4, respectively). Take 0.5 ml of a concentration of 10 6 The bacterial liquid of different strains with CFU / mL was coated on LB solid medium. After the plate was blown dry, a 0.2ml pipette tip was used to punch holes in the medium. After picking out with a needle, 0.1ml of different concentrations of drug solution was added to each well. 20% DMSO solution was used as a blank control. The results are shown in Figure 5 (a), (b).
[0072] Figure 5 (a) and (b) are the antibacterial performance test diagrams of dihydroquercetin. Figure 5 (a) It can be seen that dihydroquercetin has strong antibacterial activity against the four foodborne bacteria, among which the strongest inhibitory activity is against Vibrio parahaemolyticus (V. parahaemolyticus), followed by Staphylococcus aureus (S. aureus), and the results for Escherichia coli (E. coli) and Pseudomonas aeruginosa (P. aeruginosa) are similar. Figure 5 (b) The antibacterial effect can be compared more intuitively by the diameter of the transparent circle. Figure 5 (a) The results are consistent.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a zein / polyethylene oxide / dihydroquercetin nanofiber cling film, characterized in that: The following steps are involved: Dissolving zein in an acetic acid solution, then adding polyethylene oxide to obtain a zein / polyethylene oxide blended solution, adding dihydroquercetin to the zein / polyethylene oxide blended solution, and mixing them evenly to obtain a spinning solution; The spinning solution is treated by a solution blowing spinning process to obtain a zein / polyethylene oxide / dihydroquercetin nanofiber cling film.
2. The method for preparing the zein / polyethylene oxide / dihydroquercetin nanofiber fresh-keeping film according to claim 1, characterized in that: The specific process of solution blowing spinning is: Transfer part of the spinning solution to the injection container, bend the needle head to 90° and install it on the micro-injection pump, adjust the solution advancement speed, turn on the air compressor for blowing, adjust the spinning air pressure and receiving distance, and stick a circle of release paper on the receiver for subsequent separation, adjust the receiver speed, click the start button on the injection pump, and start spinning.
3. The method for preparing the zein / polyethylene oxide / dihydroquercetin nanofiber fresh-keeping film according to claim 2, characterized in that: The parameters of solution blowing spinning process are: The injection container is a 5 mL syringe, the needle model is 30G, the solution advancement speed is 1 mL / h, the spinning gas pressure is 0.020 MPa, the receiving distance is 50 cm, and the receiver rotation speed is 100 r / min.
4. The method for preparing the zein / polyethylene oxide / dihydroquercetin nanofiber fresh-keeping film according to claim 1, characterized in that: The mass ratio of zein, polyethylene oxide and dihydroquercetin is 2:0.1:(0.1-0.4).
5. The method for preparing the zein / polyethylene oxide / dihydroquercetin nanofiber fresh-keeping film according to claim 1, characterized in that: The specific preparation process of the spinning solution is as follows: after the acetic acid solution is prepared, zein is first added in proportion, stirred for 3 minutes until there is no lumpy powder, polyethylene oxide is added, mixed evenly until there are no obvious lumpy particles, and then dihydroquercetin is added while stirring, stirred overnight at room temperature until it is completely dissolved, to obtain a spinning solution.
6. The method for preparing the zein / polyethylene oxide / dihydroquercetin nanofiber fresh-keeping film according to claim 1, characterized in that: The volume ratio of acetic acid to water in the acetic acid solution is 8:
2.
7. A zein / polyethylene oxide / dihydroquercetin nanofiber fresh-keeping film, characterized in that: The method according to any one of claims 1 to 6 is used to prepare the product.
8. The zein / polyethylene oxide / dihydroquercetin nanofiber fresh-keeping film according to claim 7, characterized in that: The fibers in the nanofiber cling film are evenly distributed and have a diameter of 360 nm.
9. Application of the zein / polyethylene oxide / dihydroquercetin nanofiber cling film according to claim 7 or 8 in food packaging materials and biomedicine.
Citation Information
Patent Citations
Quercetin inclusion compound electrospining nanofilm and preparation method and application thereof
CN105568552A
Edible corn protein-based food packaging material and preparation method for same
CN106567143A
Zein / polyphenol / nano-zinc oxide composite fiber membrane and preparation method thereof
CN113897734A
Functional double-layer nanofiber membrane prepared by solution blowing spinning and application of functional double-layer nanofiber membrane
CN117488479A
Cited By
Antistatic treatment process of resin-based polyester fiber
CN121046980A
Corn protein-based composite film capable of synergistically degrading ethylene and resisting bacteria and preparation method of corn protein-based composite film
CN122344408A